Comminuted, Articular Fractures of the Olecranon Process in Horses: 17 Cases (1980 to 1990) - Anderson, D. E.; Allen, D.; DeBowes, R. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Case records of 17 horses with a radiographic and surgical diagnosis of comminuted, articular fracture of the olecranon process of the ulna were retrieved using a computer-assisted search of hospital records entered between January 1, 1980 and October 31, 1990. The records were reviewed, and case management data summarized. Radiographic images were retrieved, and descriptions of the fractures recorded. Horses were classified as survivors if they were discharged from the hospital. Follow-up information was obtained by examination or phone conversation with the referring veterinarian, owner or trainer.Twelve horses (71%) survived to be discharged from the hospital. Survivors were significantly younger and weighed less (mean age, 3.9 years; mean body weight 290.2 kg) than non-survivors (mean age, 9.1 years; mean body weight, 412.2 kg). Breed, gender, and duration of clinical signs prior to surgery were not significant to the outcome. Seven horses admitted with open wounds, and two horses suffered sepsis of the surgical site after internal fixation. Of these nine horses, four (44%) were discharged from the hospital. Patients with sepsis of the fracture site, because of open wounds or postoperative infection, had a significantly lower survival rate than horses in which asepsis of the fracture site was maintained.Follow-up information was available for eight of 12 survivors (mean followup period, 2.6 years). Five (63%) horses were riding or “training sound” at the time of follow-up. Of five horses less than one year of age at the time of surgery, three (60%) were sound at a mean of 1.2 years after surgery. Of three horses four years or older, two (66%) were sound at follow-up 3.7 years after the operation.Comminuted, articular fractures involving the olecranon process can be managed successfully in horses using a dynamic compression plate applied to the caudal aspect of the ulna. Also, application of a second plate on the lateral aspect of the ulna is possible, when fracture instability has been noted after application of the caudal plate. Age, weight, and sepsis of the fracture site were the most important prognostic indicators in this study.Historical data, physical examination findings, surgical findings, clinical management data, and follow-up information are reported for 17 horses affected with comminuted, articular fracture of the olecranon process. Twelve (71%) horses survived to be discharged from the hospital. Survivors were significantly younger and of lighter body weight than non-survivors. Horses in which sepsis of the fracture site occurred had a significantly lower survival rate than horses in which aseptic fracture environment was maintained. Of eight horses available for follow-up information, five (63%) were riding or training sound at a mean of 2.6 years after surgery.
Keywords: Horse; Olecranon; Ulna; Fracture; Comminuted; Articular